Dinamika Sosial Ekonomi Pekerja Sektor Informal Di Kota Jambi: Studi Kasus Pada Kawasan Car Free Day - Seftiani, Yoranda (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to analyze the socioeconomic characteristics of informal sector workers and the factors influencing the income of business owners in the Telanaipura Car Free Day (CFD) area, Jambi City. The study used a quantitative approach with primary data obtained through questionnaires distributed to 96 respondents selected using purposive sampling techniques. Data analysis was conducted descriptively and inferentially using multiple linear regression. The independent variables in this study include digital technology, operational capital, working hours, and business duration, while the dependent variable is business owner income. The results show that simultaneously all independent variables significantly influence the income of informal sector workers. However, partially only operational capital and business duration have a positive and significant effect on income. Digital technology has a positive but insignificant effect, while working hours have a negative and insignificant effect on income. The research findings also indicate that the majority of informal sector workers are of productive age, have varying levels of education, and are dominated by micro-entrepreneurs with limited capital. This study confirms that the increase in income of informal sector workers is more influenced by business capacity and business experience than the use of digital technology or increasing working hours. Therefore, strengthening access to capital and developing business capacity are important strategies in improving the welfare of informal sector workers in urban areas.